Trans-aquatorial Clustering within the Trend of Cross-border International Economic Interactions - Druzhinin, Alexandr G.; Gorochnaya, Vasilisa V.; Dets, Igor A.; latchninsky, Stanislav S.; Mikhaylov, Andrey S.; Volkhin, Denis A. (International Journal of Economics and Financial Issues, 2016)
The article is devoted to the issues of cross-border clustering in coastal areas. The subject of the research is studied in the context of the modern globalization trends. The authors provide the classification of the cross-border clusters according to the vector of “coastalization” and “thalass-attractiveness” of the international economic processes. As the result, the new phenomenon of trans-aquatorial cluster, multiple types of its structure, are studied with the use of the modeling, classification, comparative and structural analysis methods. Using the means of logic and mathematical modeling the special peculiarities of cross-border and trans-aquatorial clusters are identified. The special attention is paid to the role of international ports and logistic complexes within the creation of conditions for the cross-border clustering in coastal areas. The empirical evidence of the research includes the typical cases of cross-border clustering with the features of trans-aquatorial interaction in European Union, Asia and Russia. Analyzing the development of trans-aquatorial clusters in the “growth triangles” in Asia regions, as well as in the North-West of Russia and Europe, the authors study the role of governmental initiative and international logistic port complexes in the process of regional economic development that results in the effective economic growth though the means of trans-aquatorial clustering. Keywords: economic cluster, cross-border cluster, trans-aquatorial cluster, coastal areas JEL Classifications: F23, F55, F63, R12